Organized Crime in Brazilian Prisons: The Example of the PCC - Dias, Camila Nunes; Salla, Fernando (International Journal of Criminology and Sociology, 2013)
This paper analyses the context of the mass incarceration experienced by Brazil in the last two decades. Alongside other factors, such as the deterioration of the living conditions of the inmates and the shortcomings in the prison management, this favored the emergence and operation of the self-named group Primeiro Comando da Capital (PCC) (First Command of the Capital), within the prison system of the state of São Paulo. It outlines the stages that resulted in the expansion of the PCC, from its creation to the consolidation of its rule over the incarcerated population and analyzes the form acquired by the use of violence by part of this group. Besides the use of official documents, the ethnographic method and interviews with staff and inmates were used. Among the major findings of the research, there is the constitution of the PCC as a centralized instance of mediation and conflict resolution within the prison, a phenomenon that produced a significant reduction in physical violence among prisoners.